Dividend policy and institutional holdings: Evidence from Australia - Thao Nguyen; Hui Li (International Journal of Financial Studies, 2020)
This paper investigates the relationship between dividend payout and institutional ownership for all Australian listed firms in the period between 2001 and 2015. In our univariate tests, we find that institutional investors, in general, prefer dividend-paying firms more than non-paying firms, and for the dividend-paying firms in our sample, institutional investors hold more shares in the firms who pay higher dividends. We further explore the causality between dividend payout and institutional ownership in our multivariate tests with our panel data. The results show an insignificant effect of institutional ownership (dividend payout) on the future dividend payout (institutional ownership) while controlling for firms' fundamentals, that a higher dividend yield does not attract more institutional investors and that there is no catering to Australian institutional investors.
Keywords: G30; G35; 330; Australian study; dividend policy; imputation tax system; institutional investor